Antibacterial Activity of the Secondary Metabolite of Fusarium LBSU Isolate from the Cat’s Whiskers Plant (Orthosiphon stamineus) - Sati Agriani Zega Zega; Rico Halim; Astri Natalia Ginting; Finna Piska (Universitas Pahlawan Tuanku Tambusai, 2025)
The cat's whisker plant is known to contain bioactive metabolites that have potential as therapeutic agents, while its rhizosphere is a habitat for microorganisms that produce secondary metabolites. Fusarium LBSU isolate were isolate from the rhizosphere of cat’s whiskers plant. Secondary metabolites are produced through liquid fermentation, followed by extraction using ethyl acetate. Antibacterial activity was tested using the disk diffusion method against the Escherichia coli and Staphylococcus aureus. The highest antibacterial activity obtained against Escherichia coli 23.565 mm, higher than Staphylococcus aureus which is 15.3 mm. These findings support the further development of secondary metabolites from rhizosphere isolate as an alternative source of environmentally friendly and effective antibacterial agents.